Single-atom iron on silicon carbide surfaces as catalyst of Fischer-Tropsch-type reactions in astrophysical environments - Pareras, Gerard; Rimola, Albert (Frontiers in Astronomy and Space Sciences, 2025)
Silicon carbide (SiC) is a major component of interstellar dust in carbon-rich environments, but its catalytic potential in space has remained largely unexplored. In this work, we investigate how single iron atoms supported on SiC (Fe0@SiC) can drive Fischer Tropsch-type (FTT) reactions, transforming the two most abundant gas-phase species in the interstellar medium (H2 and CO) into more complex organic compounds, i.e., formaldehyde (H2CO) and methanol (CH3OH). Using density functional theory (DFT), we model the catalytic cycle on the most stable β-SiC (110) surface, revealing that H2CO forms efficiently with relatively low activation barriers (up to 18.3 kcal mol−1), while, in contrast, CH3OH formation faces a significant energy barrier (32.6 kcal mol−1) in space. Atomistic mechanistic study highlights the role of Fe0@SiC in stabilizing reaction intermediates through Fe-H-Si bridging interactions, which facilitate H2 activation and CO hydrogenation. Kinetic analysis suggests that H2CO and CH3OH formation is viable in regions with temperatures above 200 and 350 K, respectively, aligning with observations of formaldehyde and methanol in protoplanetary disks and comets. The findings also suggest that FTT processes could contribute to the formation of other organic molecules, such as acetaldehyde and short-chain hydrocarbons, in space. This work offers new insights into how cosmic dust grains might drive the formation of complex molecules during the planetary system formation.